Investigation of the Movement of Cotton Seeds along the Groove Formed on the Surface of the Grate in the Working Chamber of the Saw Fiber Separator - Shokirov Khasanboy; Sarimsakov Olimjon (International Journal on Orange Technologies, 2021)
Currently, much attention is paid to increasing the output of value-added finished products, improving the cotton industry system based on the deep processing of cotton raw materials, lowering production costs and improving the quality of cotton products based on the re-equipment of cotton primary processing technology.